Sosialisasi Pengolahan Sampah Organik Rumah Tangga dengan Maggot BSF di Desa Gelam Kabupaten Sidoarjo - Binti Azizatun Nafi’ah; Ahmad Bagus Rohim; Minanti Dwi Setianingrum; Almeyda Ashfi Raihan; Aurelia Selvira Oliviani; Maulida Choirunnisa; Elmira Zachra Putri Hamidun; Muhammad Rizqi Raihan Bakir; Satria Farras Athallansyah (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The village of Gelam village in Sidoarjo is one of the areas facing a significant problem with the accumulation of organic waste. To address this issue, this community is processing organic waste using Black Soldier Fly (BSF) maggots. The training methods include location surveys, socialization, and direct education to the community about organic waste processing using BSF maggots. The results of this activity show that the community has understood the method of processing waste using BSF maggots and is interested in conducting small-scale maggot cultivation. This activity also helps reduce organic waste accumulation and creates new job opportunities. Therefore, it is the standard of the community in Gelam village.